Environment-friendly AgNWs/Ti3C2Tx transparent conductive film based on natural fish gelatin for degradable electronics - Wang, Yuzhou; Wang, Tao; Liu, Yan; Geng, Hong-Zhang; Zhang, Lianzhong (Frontiers in Chemistry, 2022)
Recently, the electronic waste (E-waste) has become the most serious environmental trouble because of the iteration of electronic products. Transparent conductive films (TCFs) are the key component of flexible electronic devices, so the development of devices based on degradable TCFs has become an important way to alleviate the problem of E-waste. Gelatin, one of the most prevalent natural biomacromolecules, has drawn increasing attention due to its good film-forming ability, superior biocompatibility, excellent degradability, and commercial availability at a relatively low cost, but has few applications in flexible electronics. Here, we report a method for preparing flexible TCF based on naturally degradable material-fish gelatin, in which silver nanowires and Ti3C2Tx flakes were used as conductive fillers. The obtained TCF has low roughness (RMS roughness = 5.62 nm), good photoelectric properties (Rs = 25.2 Ω/sq., T = ca.85% at 550 nm), strong interfacial adhesion and good degradability. Moreover, the film showed excellent application in the field of EMI shielding and green light OLED device. We believe that these TCFs will shine in the smart wearable field in the future.